Polynomial extensions of generalized quasi-Baer rings - Ghalandarzadeh, S.; Javadi, H. S.; Khoramdel, M. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
In this paper, we consider the behavior of polynomial rings over generalized quasi-Baer rings and show that the generalized quasi-Baer condition on a ring R is preserved by many polynomial extensions.